Orthogonal Frequency Division Multiplexing Modelling - Katsiru, Noah Kudakwashe (Department of Electrical Engineering, 2022)
This work is motivated by the need to understand the performance of Orthogonal Frequency Division Multiplexing (OFDM) and Filterbank Multicarrier (FBMC). Multicarrier techniques are widely being considered for the development of the telecommunication systems such as the Long Term Evolution (LTE) networks, 5th Generation (5G) and beyond. One of the modulation strategies for upcoming 5G mobile communication technologies is FBMC. When compared to OFDM, which is utilised in Fourth Generation (4G) mobile communications technology, it employs multicarrier techniques that are immune to fading produced by transmission of more than one route at a time and also resistant to intersymbol interference. OFDM is one of the popular and highly recommended modulation schemes for LTE applications. OFDM is used for communications and is found in modern digital communication systems (e.g. WiFi, 4G, etc.). OFDM transmits streams of data in many orthogonal sub-carrier frequencies at varying data rates. These carriers do not interfere with each other and thus mitigate inter-symbol interference (ISI) and inter-carrier-interference (ICI). The simulation of an OFDM modulation technique, as well as the performance of OFDM in contrast to an FBMC modulation scheme in terms of delivering the same quantities of data, will be investigated using an ideal communication channel and replicated in a multipath fading channel. Using OFDM modulation techniques, a multipath channel was investigated for realistic simulations. In MATLAB, a picture was used as the input signal to identify the OFDM modulation method with the lowest bit error rate (BER). Quadrature amplitude modulation (QAM) was examined using 16QAM, 32QAM and 64QAM, Binary phase shift keying (BPSK), eight phase shift keying (8PSK), quadrature phase shift keying (QPSK), 16QAM, 32QAM and 64QAM OFDM modulation techniques were used. Channel noise is modelled by adding a white Gaussian noise (AWGN). The channel noise variance decreases with an increase in signal to noise ratio (SNR). 10dB SNR and 20dB SNR inputs were used in the simulations to obtain the BER of the recovered image. QPSK modulation scheme in a multipath fading system produced bit error rates which are higher than BER produced in BPSK modulation scheme. 8PSK modulation scheme produced a higher BER compared to BER of BPSK modulation scheme at the same input SNR. As the modulation order increased the BER increased. 64QAM has the highest BER. Frequency and Phase offsets resulted in symbol error rates increasing as the channel impairments increased in FBMC. The spectral efficiency of OFDM is higher than FBMC spectral efficiency at low burst durations. High burst duration results in FBMC spectral efficiency getting higher than OFDM spectral efficiency. Mild impairments rarely caused symbol recovery errors, but the harsh impairments caused multiple symbol errors. To reduce and eliminate the effects of multipath fading, the least squares channel estimation method is used.